Information Processing Biases and Attachment Styles in Adolescents with Dissociative Disorders - Ritwika Nag; Nishant Goyal; Madhumita Bhattacharyya (Indian Journal of Psychological Medicine)
Background: Dissociative disorders invade and interfere with the person’s continuity of normal psychological functioning and exhibit slower or impaired processing of threat-related information and attachment styles play a significant role in their psychopathology. The present study assessed the type of attachment style and information processing biases and their relationship in adolescents with dissociative disorders. Methods: This was a hospital-based study, with a cross-sectional design based on purposive sampling. The study consisted of 50 participants between 11 and 17 years of age. Twenty-five of them were adolescents diagnosed with dissociative disorders and 25 were healthy adolescent controls. The Adolescent Dissociative Experiences Scale was used to assess the severity of dissociative disorders in adolescents. Emotional Stroop, Emotion Face dot-probe task and attachment style questionnaires were administered. Results: Findings suggested an association between the scores in the attachment style dimension of discomfort with closeness and information-processing biases in both the dot-probe and emotional Stroop tasks. There was also an association between the processing bias in the dot-probe task and relationships as a secondary attachment dimension. There was a difference in the two groups of adolescents with dissociative disorders and matched healthy adolescents with respect to the discomfort with closeness attachment style and information-processing bias scores of the dot-probe task. Conclusion: The study provides interesting insights into how information-processing biases correlate to attachment styles in adolescents with dissociative disorders. Results indicate extensive resources for future management.